An Improved Rectenna Design For Rf Energy Harvesting - E_, Sun Ye (2017)
Nowadays, Radio Frequency (RF) energy harvesting has become increasingly popular in green technology due to the high rise of the television base stations, mobile phone base stations, Wi-Fi, Bluetooth and others. Many researches have been done on harvesting the RF energy. However, the RF energy available around is still too small and the conversion efficiency at the multiplier part is very low. Thus in this research, an improved rectenna design for RF energy harvesting circuit for WSN application has been designed to harvest the RF energy from a dedicated and ambient sources is presented. This research presents three rectenna design which focusing at three different frequencies which are GSM 900, GSM 1800 and Wi-Fi band due to the availability of those signal around us. This research is progressed in few stages involving designs of multiplier circuit, designs of antenna, test and measurement of each part, combination of multiplier and antenna to form rectenna and rectenna test and measurement. Rectenna operating at 915 MHz is able to achieve an output voltage of 0.115 V when harvesting RF signal from Nokia 100 at a distance of 30 cm. 0.067 V can be measured when 915 MHz rectenna harvest RF energy around USM. Rectenna operating at 1.8 GHz able to achieve an output voltage of 0.273 V when it harvest the RF energy from Nokia 100 at a distance of 30 cm. When the rectenna harvest the ambient RF Energy, 0.042 V of output voltage can be measured. Additionally output voltage of 0.214 V can be achieved when the 2.4 GHz rectenna harvest RF energy from a TP-Link modem router with a distance of 50 cm. A 0.037 V of output voltage can be obtained when 2.4 GHz rectenna is harvesting ambient RF energy. The designed rectenna are able to perform well under three conditions or environments. Subsequently they show significant improvements over other related works and in turns have space for further improvement in the future.